2016
DOI: 10.1021/acs.jpcc.5b12105
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity Comparison of Indium Gallium Zinc Oxide Thin Films: Dependence on Temperature, Crystallinity, and Porosity

Abstract: The cross-plane thermal conductivity of In-GaZnO (IGZO) thin films was measured using the 3ω technique from 18 to 300 K. The studied morphologies include amorphous (a-IGZO), semicrystalline (semi-c-IGZO), and c-axis-aligned single-crystal-like IGZO (c-IGZO) grown by pulsed laser deposition (PLD) as well as a-IGZO deposited by sputtering and by solution combustion processing. The atomic structures of the amorphous and crystalline films were simulated with ab initio molecular dynamics. The film quality and textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 62 publications
6
24
0
Order By: Relevance
“…Over the past few years, amorphous indium-gallium-zinc-oxide (IGZO) has become a promising active channel material for thin-film transistors (TFTs) which have been utilized in different types of electronics, including display backplanes and sensor arrays 1–3 . This is due to its excellent material properties of superb mechanical stability, good electrical conductivity, and optical transparency 46 . Compared to silicon-based materials, metal-oxide semiconductors exhibit relatively good electrical characteristics even in an amorphous phase 79 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, amorphous indium-gallium-zinc-oxide (IGZO) has become a promising active channel material for thin-film transistors (TFTs) which have been utilized in different types of electronics, including display backplanes and sensor arrays 1–3 . This is due to its excellent material properties of superb mechanical stability, good electrical conductivity, and optical transparency 46 . Compared to silicon-based materials, metal-oxide semiconductors exhibit relatively good electrical characteristics even in an amorphous phase 79 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent experiments also showed that the thermoelectric conductivity of partially crystalline TCO films is higher compared to amorphous or crystalline films. 13 Commonly used TCOs and AOSs consist of oxides of indium, tin, gallium, cadmium, and zinc. Indium-tin oxide (ITO) is obtained by doping indium oxide (IO) with tin.…”
Section: Introductionmentioning
confidence: 99%
“…12 The thermal conductivity of semi-crystalline indium-gallium zinc oxide (IGZO) films can also be higher than that of amorphous or fully crystalline samples. 13 A better understanding of the depth and lateral uniformity of the crystalline films is also crucial in understanding specific properties. For example, in materials such as graphene oxide, the in-plane and crossplane thermal conductivities can vary by a factor of 675.…”
Section: Introductionmentioning
confidence: 99%
“…al demonstrated that the porosity of spin-coated CS-processed indium gallium zinc oxide (IGZO) film (~50 nm-thick) can be as high as 40 %, which seriously deteriorates its functional properties. 25 In this work, we take CS-derived indium tin oxide (ITO) conductive metal oxide thin films processed at 350 o C as a model system to explore the porosity problem and improve their electrical ARTICLE Materials Advances…”
Section: Introductionmentioning
confidence: 99%